2021
DOI: 10.1017/s0007114521003172
|View full text |Cite
|
Sign up to set email alerts
|

Allulose in human diet: the knowns and the unknowns

Abstract: D-Allulose, also referred to as psicose, is a C3-epimer of D-fructose used as a sugar substitute in low calorie products. It can be formed naturally during processing of food and drinks containing sucrose and fructose or is prepared by chemical synthesis or via enzymatic treatment with epimerases from fructose. Estimated intakes via western style diets including sweetened beverages are below 500 mg per day but, when used as a sugar replacement, intake may reach 10 to 30g per day depending on the food consumed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…However, despite the existence of beneficial aspects of the use of allulose, in vitro studies have shown that bacteria such as Klebsiella pneumonia (an opportunistic human pathogen) can utilize allulose as a substrate. This raises the question of whether a high dietary intake of D-psicose may contribute to the growth of potentially harmful bacteria at mucosal sites such as the intestine [ 113 ].…”
Section: Techniques Used In Reducing the Sugar Content Of Juicesmentioning
confidence: 99%
“…However, despite the existence of beneficial aspects of the use of allulose, in vitro studies have shown that bacteria such as Klebsiella pneumonia (an opportunistic human pathogen) can utilize allulose as a substrate. This raises the question of whether a high dietary intake of D-psicose may contribute to the growth of potentially harmful bacteria at mucosal sites such as the intestine [ 113 ].…”
Section: Techniques Used In Reducing the Sugar Content Of Juicesmentioning
confidence: 99%
“…8 Additionally, D-allulose is not involved in glucose metabolism, is not metabolized in hepar, does not alter pancreatic and insulin function, and does not influence post-prandial blood glucose levels. 7,11,13,14 Most of the D-allulose was excreted in the form of urine. Only a small part of D-allulose is excreted in faecal form.…”
Section: Role Of D-allulose Treatment On Blood Glucose Levelmentioning
confidence: 99%
“…Furthermore, it is not influencing pancreatic function nor altering the blood glucose level. 7,11,13,14 Recently, despite its role as a safe sweetener, evidence has elucidated potential medicinal role of D-allulose as an anti-diabetic through its role as an insulin mimetic and modulator of some insulin-responsive genes. 11 Our result confirmed previous findings that once daily treatment of 0.1 g/kg BW D-allulose significantly reduces post-prandial blood glucose levels in the diabetic rats on days 56 and 84 compared to their diabetic counterparts without treatment, though the blood glucose level reduction did not reach normal levels (Table 1).…”
Section: Role Of D-allulose Treatment On Blood Glucose Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…The EU introduced D-tagatose as a new food ingredient (18) . Many kinds of rare sugar containing foods have already been marketed in several countries, including the USA, EU and Japan (1921) .…”
mentioning
confidence: 99%